Year of birth and sperm count in 10 Danish occupational studies - Bonde, Jens Peter E.; Kold Jensen, T.; Brixen Larsen, S.; Abell, A.; Scheike, T.; Hjollund, N. H. I.; Kolstad, Henrik A.; Ernst, E.; Giwercman, A.; Skakkebæk, Niels Erik; Keiding, N.; Olsen, Jørn (Scandinavian Journal of Work, Environment & Health, 1998)
' ' OBJECTIVES ': 'Several reports indicate a secular decline of human sperm counts. It is still not known if these findings are artifacts related to shortcomings in the data and applied methodologies. Even less is known about possible mechanisms, but it has been proposed that potential changes may be related to disruption of the hormonal regulation of testicular development in prenatal life. The objective of this study was to examine whether sperm count was related to year of birth.' ' METHODS ': 'An analysis was made of the sperm count of 1196 men participating in 10 cross-sectional occupational sperm studies in 3 regions of Denmark from 1986 through 1995.' ' RESULTS ': 'The median sperm concentration was 63 million per milliliter for men born in 1937-1949 and 52 million per milliliter for men born in 1970 or later, and the median total sperm was 206 million and 117 million, respectively. The inverse relationship between sperm concentration and year of birth was statistically significant even after adjustment for duration of sexual abstinence, season of the year, and study population. However, bias because of differential participation related to age and fertility or lack of comparability across the populations cannot be ruled out.' ' CONCLUSION ': 'The apparent decline of sperm count with increasing year of birth is compatible with the hypothesis of a common risk factor for male reproductive health operating in prenatal life or early childhood, but the evidence is circumstantial. Age-related selection bias is an alternative and perhaps not a less likely explanation.
Keywords: birth cohort; Denmark; environment; epidemiology; male; occupational study; reproduction; secular trend; semen; sperm concentration; sperm count; sperm density; year of birth